PENDEKATAN KOMITMEN KERJA MELALUI PERAN GANDA DAN STRESS KERJA - Astuti, Dwi; Lian, Bukman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2018)
The problems faced by private organizations and government agencies, especially in Palembang were about the female employees who have double roles and levels of work stress they face. This is certainly a challenge for every private organization and government agencies in order to improve the quality of organizational commitment through work professionalism. Employees who have multiple roles may have severe problems, they tend to often experience work stress conflicts, because their role as an employee is difficult regardless of the role of housewife. The purpose of this research was to know the conflict of double role and level of work stress to organizational commitment to the household worker. The respondents were a housewife who works in government agencies Public Broadcaster Radio Republic Indonesia Programa 2 South Sumatera. The results of this study indicate that the increase in commitment and professionalism of work due to field work programs for employees who have double roles. Negative effects of job stress must be minimized because it can adversely affect organizational commitment. Employees who have double roles should effectively manage time to minimize work stress as a result of double roles.